التجديد والحداثة بين محمد اقبال ومحمد عابد الجابري - مريزيق, يوسف (University of eloued جامعة الوادي, 2022)
لقد تم التطرق في هذه الدراسة إلى موضوع والتجديد والحداثة-المقارنة بين محمد إقبال ومحمد عابد الجابري-، وذلك من خلال وقوفي على معالم التجديد والحداثة عند كل وحد منهما وعمال مقارنة بينها وقد خلص في النهاية إلى أن إقبال حول بناء الفكر الديني الإسلامي من جديد وذلك بالازدوجية بين الفكر الغربي والفكر العربي، إلاّ أنّ إقبال تمسك بالأصول العربية والإسلامية أكثر، أمّا الجابري فقد حول بناء حداثة عربية، انطلاقا من نقده للفكر العربي المعاصر، وذلك من خلال الازدوجية بين الفكر الغربي والفكر العربي حيث عمل على تغليب النتجات الغربية على الفكر العربي المعاصر والجانب التراثي. The subject of renewal and modernity has been addressed in this study - a comparison between Muhammad Iqbal and Muhammad Abed al-Jabri-, by looking at the features of renewal and modernity in each of them and comparing them. In the end, he concluded that Iqbal is about building Islamic religious thought anew, and that In the duality between Western thought and Arab thought, however, Iqbal stuck to the Arab and Islamic origins more. As for Al-Jabri, he transformed the construction of Arab modernity, based on his criticism of contemporary Arab thought, through the duality between Western thought and Arab thought, where he worked to give priority to Western products over thought. Contemporary Arab and the traditional side.
عقيدة اسلامية
Keywords: التجديد الحداثة محمد اقبال الجابري; Renewal Modernity Muhammad Iqbal Al-Jabri